THE ECONOMIC IMPACT OF RELIGIOUS TOURISM ON DEVELOPMENT TOURISM INDUSTRY OF THE REPUBLIC OF UZBEKISTAN: ANALYSIS, EVALUATION AND PROSPECTS - Mirsaatov Jasur (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The article examines the economic impact of religious tourism on the development of the tourism industry of the Republic of Uzbekistan. Based on statistical data from the State Tourism Committee and the World Tourism Organization, the dynamics of inbound tourist flow for 2015–2023 is analyzed, and the share of religious tourism in its structure is estimated. The multiplier analysis method is applied: the total economic contribution of religious tourism, taking into account direct, indirect, and induced effects, is estimated in the range from 945 million to 1.85 billion US dollars annually, which corresponds to 1.1–2.1% of the country's gross national product. Critical regional imbalances are identified: about 90% of tourist flows are concentrated in three regions, with significant untapped potential in the Fergana Valley and Surkhandarya region. A SWOT analysis is conducted, and strategic development vectors are identified. Specific recommendations for improving the effectiveness of public policy in this area are formulated.